Pós-tratamento de efluente de reator UASB por eletrocoagulação e adsorsão para reúso - Pizutti, Janaína Terhorst (2018)
The treatment and reclaim of effluents is a concern with the management of water resources and the main consumption of fresh water is related to non-use. In order to obtain higher quality standards for reuse, effluent treatment techniques are essential. In this way, this work had an efficiency for the post-treatment of UORB domestic effluents through electrolytic and adsorption processes. In the first series, the electrocoagulation (EC) and electro -oxidation (EO) processes were evaluated with pH variations and electric current intensity in theremoval of energy and energy consumption. An optimized condition was the use of an electrocoagulation with current of 29.44 A / m2 and pH 6.0. The specific energy consumption was 31.1 kWh / kg and the removal of 44.58% of the COD. Advice on the use of a hot air filter before the adsorption process, which is considered especially heavy for a removal of suspended solids and turbidity. It was, as the breakdown curves of the adsorption operation of an increasing behavior of the residue, and the bed was not fully synthesized throughout the experiments. Compared with color removals (96.11%) and phosphorus (97.54%). The conjugated processes of electrocoagulation, sand filtration and adsorption in vapors wereadequate for the effluent, according to the physical-chemical and biological, urban, industrial, recreational and environmental work classes, according to national and international regulations.